The Effect of Noni Juice with Ambon Banana on Blood Pressure Reduction in Family with Hypertension Disease in East Jakarta - Yuli Astuti; Muhammad Fandizal; Nova Riani; Irsan Aman; Anisa Nurmala; Masruroh Masruroh (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Introduction: Hypertension is an increase in blood pressure above 140/90 mmHg into a serious medical condition that can increase the risk of heart disease, and brain and kidney disease. It is estimated that 1.13 billion people worldwide suffer from hypertension, mostly about 2/3 live in low- and middle-income countries. This disease causes an increased risk of stroke, aneurysm, heart failure, heart attack, and kidney damage. To control blood pressure, you can use natural medicine, namely noni juice with Ambon banana which contains soranjidiol, which acts as a urinary laxative and has pharmacological and diuretic properties because of its water content. which helps lower blood pressure. And potassium in Ambon banana can help lower blood pressure. Objective: This study was to determine whether noni juice with Ambon banana affects lowering blood pressure. Methods: This research method uses a quasi-experimental design by comparing blood pressure before the intervention and after the intervention. The hypothesis test used is a two-mean independent test and a dependent sample t-test with a total sample of 25 interventions and 25 controls. Sampling using a non-probability sampling technique, namely purposive sampling. Data collection tools used interviews to obtain demographic data and direct measuring tools used were a sphygmomanometer and observation sheet. Results: Before consuming Ambon noni-banana juice, the respondents' average blood pressure was 164/92 mmHg and after consuming Ambon noni-banana juice, the respondents' average blood pressure was 133/85 mmHg. Before the intervention, 60% of respondents suffered from stage 2 hypertension and 40% of respondents suffered from stage 1 hypertension. After consuming Ambon noni-banana juice, no more respondents had stage 2 hypertension, 43% of respondents had stage 1 hypertension, and 57% of respondents suffered from hypertension. pre hypertension. Based on the test results obtained p-value 0.000 <0.05, which means that the Ambon noni-banana juice affects lowering systolic blood pressure. Conclusion: People with hypertension can consume Ambon banana noni to lower blood pressure, as an alternative treatment.